Terrestrial lichen response to partial cutting in lodgepole pine forests on caribou winter range in west-central British Columbia - Waterhouse, Michaela J.; Armleder, Harold M.; Nemec, Amanda F. L. (Rangifer, 2011)
In west-central British Columbia, terrestrial lichens located in older, lodgepole pine (Pinus contorta) forests are important winter forage for woodland caribou (Rangifer tarandus caribou). Clearcut harvesting effectively removes winter forage habitat for decades, so management approaches based on partial cutting were designed to maintain continuous lichen-bearing habitat for caribou. This study tested a group selection system, based on removal of 33% of the forest every 80 years in small openings (15 m diameter), and two irregular shelterwood treatments (whole-tree and stem-only harvesting methods) where 50% of the stand area is cut every 70 years in 20 to 30 m diameter openings. The abundance of common terrestrial lichens among the partial cutting and no-harvest treatments was compared across five replicate blocks, pre-harvest (1995) and post-harvest (1998, 2000 and 2004). The initial loss of preferred forage lichens (Cladonia, Cladina, Cetraria and Stereocaulon) was similar among harvesting treatments, but there was greater reduction in these lichens in the openings than in the residual forest. After eight years, forage lichens in the group selection treatment recovered to pre-harvest amounts, while lichen in the shelterwood treatments steadily increased from 49 to 57% in 1998 to about 70% of pre-harvest amounts in 2004. Although not part of the randomized block design, there was substantially less lichen in three adjacent clearcut blocks than in the partial cuts. Regression analysis pre- and post-harvest indicated that increased cover of trees, shrubs, herbs, woody debris and logging slash corresponded with decreased forage lichen abundance. In the short-term, forestry activities that minimize inputs of woody debris, control herb and shrub development, and moderate the changes in light and temperatures associated with canopy removal will lessen the impact on lichen. Implementation of stand level prescriptions is only one aspect of caribou habitat management. A comprehensive approach should consider all factors and their interactions to maintain a viable population of woodland caribou in west-central British Columbia.